Impact Response of Quasi-Isotropic Asymmetric Carbon Fabric/Epoxy Laminate Infused with MWCNTs - Nand Kishore Singh; Prashant Rawat; K. K. Singh (Advances in Materials Science and Engineering)
Effect of embedding multiwalled carbon nanotubes (MWCNTs) on low velocity impact response of quasi-isotropic asymmetric laminate of plain woven carbon fabric/epoxy was investigated. Laminates were embedded with 0 wt.%, 2 wt.%, and 5 wt.% MWCNTs to improve impact resistance. Impact in laminates was conducted according to ASTM D7136 standard at an impact energy of 94.14 J corresponding to the impact velocity of 6 m/sec. Energy-time response, force-time response, and pyramidal damage area of laminates doped with varying weight percentage (wt.%) of MWCNTs were quantified and compared with laminate without MWCNTs. Absorbed impact energy increases by 13.53% on doping of 2 wt.% MWCNTs, whereas it decreases by 10.49% on doping 5 wt.% MWCNTs. Damage area is reduced on doping 2 wt.% MWCNTs in laminate.